How lower grade students spend their free time: The generation y scenario / Azniza Ahmad Zaini , Nor Aziah Abd.Kadir and Mohd Zahid Laton - Ahmad Zaini, Azniza; Abd.Kadir, Nor Aziah; Laton, Mohd Zahid (2012)
This study was conducted to discover how lower grade students of Generation Y at the Faculty of Business Management, UiTM Pahang spend their free time with media than other academic activities such as reading text books, doing assignments. discussion, and so forth. It is crucial for the educators and parents to understand the role of media in young people's lives as media is among the most powerful forces in young people's lives today. Media is also able to influence the generation Y students' activities during free time because they are born in the digital age. Lower achievement students at the Business Faculty, UiTM Pahang were chosen as respondents in this study. Self administered questionnaires were distributed to the respondents and the sample was obtained using a probability sampling technique. The data were analyzed using descriptive statistics. The results from this study are hoped to give useful information and can be used as a guideline to the educators and parents who are concerned with the impact of media on youth, specifically the lower grade UiTM students.